Nitrous Oxide Inhalation Sedation in Pediatric Dentistry: An overview of the available guidelines - Ibrahim, Dayang; Hussein, Alaa; Hamzah, Siti (Jordan Medical Journal, 2022)
Children with behavioral issues are usually inadequately treated using non-pharmacological behavior management techniques, making dental treatment a real clinical challenge for the practitioner. This leads to the indispensable need for advanced pharmacological techniques, such as inhalation sedation (IS). In pediatric dentistry, nitrous oxide sedation is considered the safest tool for a dental practitioner to use on uncooperative children, thus reducing the need for dental treatment under general anesthesia. To date, several sets of high-ranking evidence-based inhalation sedation guidelines are available, developed in the United States, United Kingdom, Europe, Australia, and New Zealand. This review summarizes the indications, contraindications, advantages, and disadvantages of using nitrous oxide sedation in children, and compares these in terms of inhalation sedation procedure and documentation. This review will assist the dental practitioner in developing appropriate practice regulations for safe and effective practice.